2023
DOI: 10.4103/ijo.ijo_1778_22
|View full text |Cite
|
Sign up to set email alerts
|

Acute abducens nerve palsy with acute disseminated encephalomyelitis-like presentation following COVID-19 vaccination

Abstract: We report two adult cases of abducens nerve palsy presenting immediately (within weeks) after they received the first dose of Covishield vaccination. Magnetic resonance imaging (MRI) of the brain obtained after the onset of diplopia demonstrated demyelinating changes. The patients had associated systemic symptoms. Post-vaccination demyelination typically known as acute disseminated encephalomyelitis (ADEM) associated with several vaccines is more common in children. Although the mechanism of the nerve palsy re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The third hypothesis concerns the potential side effects of vaccination. To date, however, there are only a few and isolated case reports speculating on a possible correlation between COVID vaccination and neurological side effects [ 54 , 55 ] or occurrence of venous sinus thrombosis [ 56 ] or increased risk of sinusitis/otitis [ 57 ]. Large trials, indeed, have demonstrated the safety of COVID vaccinations on these potential complications [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…The third hypothesis concerns the potential side effects of vaccination. To date, however, there are only a few and isolated case reports speculating on a possible correlation between COVID vaccination and neurological side effects [ 54 , 55 ] or occurrence of venous sinus thrombosis [ 56 ] or increased risk of sinusitis/otitis [ 57 ]. Large trials, indeed, have demonstrated the safety of COVID vaccinations on these potential complications [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the close correlation between the SARS-CoV-2 vaccine administration and the onset of the symptoms raised suspicion of post-vaccine acute disseminated encephalomyelitis (ADEM) ( 28 ). ADEM usually affects younger patients, but several cases during adulthood have also been described specifically in the context of SARS-CoV-2 vaccination ( 29 ).…”
Section: Discussionmentioning
confidence: 99%